2014
DOI: 10.4012/dmj.2013-054
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid effects of zirconia nanoparticles with aluminum borate whiskers on mechanical properties of denture base resin PMMA

Abstract: The aim of this study was to investigate the hybrid effects of ZrO 2 nanoparticles (nano-ZrO 2 ) and aluminum borate whiskers (ABWs) on flexural strength and surface hardness of denture base resin, polymethyl methacrylate (PMMA). Both nano-ZrO 2 and ABWs were modified by silane coupling agent (Z6030) before being mixed with PMMA. Various amounts of silanized nano-ZrO 2 and ABWs were mixed with PMMA to prepare ZrO 2 -ABW/PMMA composites. Flexural strength and surface hardness were evaluated using threepoint ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
106
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(113 citation statements)
references
References 29 publications
(40 reference statements)
7
106
0
Order By: Relevance
“…All of them have demonstrated their outstanding ability in enhance the mechanical behavior of resin 12) . And our previous research confirmed that both ABWs and ZrO2 were added in PMMA with certain proportion, the results showed that they could improve the mechanical properties obviously 10,11) . Another clinical problem associated with self-curing acrylic resins is the adhesion of dental plaque formed by oral microorganisms due to the PMMA's high water absorption capacity, surface porosities and materia alba configuration 13) .…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…All of them have demonstrated their outstanding ability in enhance the mechanical behavior of resin 12) . And our previous research confirmed that both ABWs and ZrO2 were added in PMMA with certain proportion, the results showed that they could improve the mechanical properties obviously 10,11) . Another clinical problem associated with self-curing acrylic resins is the adhesion of dental plaque formed by oral microorganisms due to the PMMA's high water absorption capacity, surface porosities and materia alba configuration 13) .…”
Section: Introductionmentioning
confidence: 90%
“…Two weight percentage silanized nano-ZrO 2 particles and 4 wt% silanized ABWs were mixed with PMMA powder by ball milling (XQM, Nanjing Kexi Laboratory Apparatus Research Institute, Nanjing, China) at a speed of 180 rpm (revolutions per min) for 120 min to get ZrO 2-ABWs/PMMA composites according to the previous studies 10) . TiO2, Ag/TiO2, Novaron and T-ZnOw of 3 wt% were mixed with the composites respectively.…”
Section: Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…1). However, Zhang et al (15) indicated that another way to control the filler dispersion to the PMMA matrix was to manipulate the nano-ZrO 2 /PMMA nanocomposite preparation procedure. They reported that mechanical attrition such as bead ball milling and ultrasonication could be used to resist nanoparticle clustering during the modification procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been many studies on the effect of ZrO 2 nanoparticle (nano-ZrO 2 ) addition as a filler to acrylic resin (14)(15)(16). The properties of the polymer-nanoparticle depend on the type of incorporating nanoparticles, their size and shape, as well as the concentration and interaction with the polymer matrix (16).…”
Section: Introductionmentioning
confidence: 99%